Designing a Retention Model of Human Capital with an Organizational Support Approach in Mashhad University of Medical Sciences (Qualitative Approach) - Mahshid Mojtahedi; Nazia Sadat Naseri; Farideh Hashemian Nejad; Fatemeh Heshmati Nabavi (Mashhad University of Medical Sciences, 2020)
Background: Designing a model based on human capital retention with an organizational support approach is one strategic issue for university staff. Therefore, the aim of this study is to identify the effective components to design a model for human capital retention with an organizational support approach in Mashhad University of Medical Sciences. Methods: The present study is in the category of developmental-applied research and was conducted by Delphi method in 2018-2019. A total of 32 experts, including specialists and faculty members of Mashhad University of Medical Sciences were selected by purposive sampling method. At first, the dimensions and components related to the retention of human capital and organizational support were obtained through extensive review of databases and research background. Then through several sessions, the dimensions and components were codified in three rounds based on the consensus of the members. Results: The suitable model for the human capital retention with an organizational support approach was finalized with 8 dimensions and 53 components. These factors included personal, organizational, job-motivational, environmental, organizational activities, job properties, organizational justice, and job stress dimensions. Results of Cohen's Kappa Coefficient for identified factors was 0.78 for the second phase of Delphi technique and 0.86 for the third phase of Delphi, which indicates a strong and acceptable agreement of panel members in relation to the factors of the conceptual model of research. Conclusion: According to the findings of the implementation of three stages of Delphi technique, the effective factors identified for the human capital retention with an organizational support approach in Mashhad University of Medical Sciences are eight factors which were mentioned above, and through explaining their current status, an effective step can be considered in this prominent university in Iran, and also its results can be used for other medical universities in the country.